2019
DOI: 10.5897/jpbcs2016.0600
|View full text |Cite
|
Sign up to set email alerts
|

Genetic variability studies on bread wheat (Triticum aestivum L.) genotypes

Abstract: Thirty bread wheat genotypes were tested to assess the genetic variability, among studied genotypes using alpha-lattice design at Tongo sub-center of Assosa Agricultural Research Center and Kulumsa Agricultural Research Center in 2015. Analysis of variance revealed that there were statistically significant differences among the genotypes for most of the traits at individual and across locations. From the combined analysis of variance, significant (p≤0.05) effect due to location, varieties and G×E was observed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(25 citation statements)
references
References 12 publications
(12 reference statements)
9
12
0
Order By: Relevance
“…The result was in agreement with the previous findings of Dargicho et al (2015b) and Jamil et al (2017) Low GCV coupled with low PCV values were noted for days to heading, days to maturity, grain filling period, harvest index, plant height and number of spikelets spike -1 under optimum condition. The present result is in agreement with the finding of Alemu et al (2019) who reported low GCV and PCV values for days to heading, days to maturity, Harvest index, plant height and spikelets spike -1 . A low GCV value was recorded for number of kernels spike -1 and thousand kernel weight (Table 4).…”
Section: Phenotypic and Genotypic Coefficient Of Variationsupporting
confidence: 94%
See 4 more Smart Citations
“…The result was in agreement with the previous findings of Dargicho et al (2015b) and Jamil et al (2017) Low GCV coupled with low PCV values were noted for days to heading, days to maturity, grain filling period, harvest index, plant height and number of spikelets spike -1 under optimum condition. The present result is in agreement with the finding of Alemu et al (2019) who reported low GCV and PCV values for days to heading, days to maturity, Harvest index, plant height and spikelets spike -1 . A low GCV value was recorded for number of kernels spike -1 and thousand kernel weight (Table 4).…”
Section: Phenotypic and Genotypic Coefficient Of Variationsupporting
confidence: 94%
“…Fifty genotypes exhibited mean performance superior to check (Fentalle-2) for thousand kernel weight. Different authors reported similar range of variations for spike length, spikelet spike -1 , number of kernels spike -1 and thousand kernel weight in their study (Gezahegn et al 2015;Dargicho et al 2015b;Alemu et al 2019;Ashebir et al 2020).…”
Section: Spike Character Harvest Index Biomass Yield and Grain Yieldmentioning
confidence: 56%
See 3 more Smart Citations